Fascists - Mann, Michael, 1942- (Cambridge University Press, 2004)
"Fascists presents a new theory of fascism based on intensive analysis of the men and women who became fascists. It covers the six European countries in which fascism became most dominant: Italy, Germany, Austria, Hungary, Romania and Spain. It is the most comprehensive analysis of who fascists actually were, what beliefs they held, and what actions they committed. Through this evidence we see that fascism is merely the most extreme form of "nation-statism," which was the dominant political ideology of the twentieth century. Fascists argued that an "organic nation" and a strong state that was prepared to use violence to "knock heads together" could transcend the conflicts, especially the class conflicts, rending modern society. We also see the fascist core constituencies: social locations that were at the heart of the nation or closely connected to the state, and people who were accustomed to use violence as a means of solving social conflicts and who came from those sections of all social classes that were working outside the front lines of class conflict. The book suggests that fascism was essentially a product of post-World War I conditions in Europe and is unlikely to reappear in its classic garb in the future. Nonetheless, elements of its ideology remain relevant to modern conditions and are now reappearing, though mainly in different parts of the world."--Jacket